2016
DOI: 10.3389/fpsyg.2016.01859
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Detection of Poetic Harmony by the Naïve Brain

Abstract: The power of poetry is universally acknowledged, but it is debatable whether its appreciation is reserved for experts. Here, we show that readers with no particular knowledge of a traditional form of Welsh poetry unconsciously distinguish phrases conforming to its complex poetic construction rules from those that violate them. We studied the brain response of native speakers of Welsh as they read meaningful sentences ending in a word that either complied with strict poetic construction rules, violated rules of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…But what is specific about poetry? Beaugrande (1978 , p. 24) proposed that “readers have as part of the text-type frame the instructions to attend to sound recurrences in the assumption that these are not random.” Previous research on the processing of poetry has confirmed that sound recurrences influence how verbal stimuli are processed ( Hoorn, 1996 ; Menninghaus et al, 2014 ; Obermeier et al, 2015 ; Chen et al, 2016 ; Vaughan-Evans et al, 2016 ) and evaluated ( Van Peer, 1990 ; Obermeier et al, 2013 ; Menninghaus et al, 2014 , 2016 ; Kraxenberger and Menninghaus, 2016 ). It can, however, not be taken for granted that these results indeed reflect adapted processing routines and increased attention to phonological structure due to genre awareness.…”
Section: Introductionmentioning
confidence: 92%
“…But what is specific about poetry? Beaugrande (1978 , p. 24) proposed that “readers have as part of the text-type frame the instructions to attend to sound recurrences in the assumption that these are not random.” Previous research on the processing of poetry has confirmed that sound recurrences influence how verbal stimuli are processed ( Hoorn, 1996 ; Menninghaus et al, 2014 ; Obermeier et al, 2015 ; Chen et al, 2016 ; Vaughan-Evans et al, 2016 ) and evaluated ( Van Peer, 1990 ; Obermeier et al, 2013 ; Menninghaus et al, 2014 , 2016 ; Kraxenberger and Menninghaus, 2016 ). It can, however, not be taken for granted that these results indeed reflect adapted processing routines and increased attention to phonological structure due to genre awareness.…”
Section: Introductionmentioning
confidence: 92%
“…The data of 20 native English speakers (16 females, mean age = 22, SD = 2.97) were included in the analysis (a further 5 were excluded owing to technical failures and/or excessive alpha contamination). This sample size was determined on the basis of recent similar studies (e.g., Chen et al, 2016;Vaughan-Evans et al, 2016). All participants had normal or corrected-tonormal vision and reported no past or present diagnosis of a learning difficulty.…”
Section: Participantsmentioning
confidence: 99%
“…Recent work in neurocognitive poetics suggests that stylistic prosodic features in phrases, such as phonological repetition, attract more attentional resources and that their neural representations are more strongly activated than those of neutral, declarative forms, as shown in behavioural (e.g. Carminati, Stabler, Roberts, & Fischer, 2006;Yaron, 2002;Tillmann & Dowling;Hanauer, 1996) and in eventrelated potential (ERP; Chen et al, 2016;Obermeier et al, 2013;, 2007;Vaughan-Evans et al, 2016) studies.…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects have even been shown in cases where rule learning was not embedded within the experiment but rather occurred from natural exposure to language. For example, Vaughan-Evans et al ( 2016 ) recently showed that the brains of individuals with no recorded or overt knowledge of an ancient form of Welsh poetry (Cynghanedd) successfully identified correct forms from sentences violating composition rules, despite being unable to detect the correct forms in overt judgement tasks. Presumably, these participants learned the rules of Cynghanedd implicitly, through natural language exposure and required no conscious knowledge.…”
mentioning
confidence: 99%